Host country corruption and the organization of HQ–subsidiary relationships - Rabbiosi, Larissa; Santangelo, Grazia D (Journal of International Business Studies, 2019)
Multinational enterprises (MNEs) operating in more corrupt host (than home) countries face actual costs related to processing information for decision-making, and lack of local legitimacy, and potential reputation and legal costs in case of corruption scandals. Drawing on the organizational perspective of corruption, we argue that greater subsidiary autonomy helps minimize these costs. However, headquarter (HQ)–subsidiary communication weakens the autonomy-based advantages for minimizing legitimacy costs, and MNEs’ experience in relatively corrupt countries weakens the advantages for minimizing information-processing costs. Our analysis of 261 Italian foreign subsidiaries in 25 host countries confirms most of our arguments except the moderating effect of MNE experience. Our findings contribute to research on corruption and FDI, weak institutional contexts and MNE strategies as well as the literature on HQ–subsidiary relationship.